PEMANFAATAN ABU LAYANG (FLY ASH) SEBAGAI ADSORBEN PADA MINYAK JELANTAH - Wogo, Hermania Em; Bokay, Ernawati A.; Tawa, Bibiana D.; Ledoh, Sherlly M. F. (Chemistry Notes, 2020)
A research on the conducted on the use of fly ash as an adsorbent in used cooking oil. This research was conducted with the aim to know the characteristics of fly ash without activation and activation with 6M HCl and to improve the quality of used cooking oil from adsorbent processing based on the Indonesian national standard (SNI). This research was conducted in several stages, namely surface acidity with the titration method, determination of surface area with the blue methylene method, determination of functional groups by FTIR analysis and oil quality based on parameters of acid number, peroxide number and smoke point. The results showed that the acidity of the surface of the fly ash was activated and without activation of 4 and 3.6 m2 / g respectively. surface area of ​​fly ash without activation 17,480 m2/g at contact time 80 and activated fly ash 18,471 m2/g at contact time 70. FTIR spectra of fly ash without activation 795,38 and 779.95 cm-1 and activated 795.38 and 778,02 cm-1 which is a symmetrical stretching adsorption band of symmetric ≡Si-O (≡Si-O-Si≡). Fly ash used for refining used cooking oil (2,468 mg KOH / g) is able to reduce the acid number 0.361 mg KOH / g in activated fly ash and 0.561 mg KOH / g for fly ash without activation, the peroxide number for activated fly ash decreased by 72.34% compared to fly ash without activation 69.14%, oil smoke point purification results from activated fly ash 203ºC and without activation 210ºC which is close to the new oil smoke point value of 200ºC. When compared with SNI, the values ​​of acid numbers, peroxide numbers and smoke points meet the standard.